Kelayakan lokasi budidaya ikan di Danau Tondano ditinjau dari parameter fisika kimia air - Kamsuri, Agus I; Pangemanan, Penky N.L; Tumbol, Reiny A (Universitas Sam Ratulangi, 2013)
The purpose of this study was to determine the current condition of the water quality of Lake Tondano in terms of physical and chemical parameters in a fish farming locations on Lake Tondano waters. Determination of sampling points at each station is placed vertically at three predetermined points from the guard house toward the front of the net, the distance between one point to the next point was Â± 10 m; whereas for the analysis of water quality parameters was done in Clinical Pathology of Fish Diseases Laboratory, Faculty of Fisheries and Marine Science, Sam Ratulangi Manado and Manado Industrial Research and Standards Laboratory. Determination points were done by purposive sampling which refers to the physiographic location wherever possible in order to represent or describe these waters. The research was carried out for 6 weeks and was done in 2 stages, morning and afternoon. For direct measurement (in situ) was performed once a week which included parameters DO, pH, temperature, and brightness, while the laboratory tests were conducted for 2 weeks which included parameters Nitrite, Nitrate, Iron, Chlorine, Manganese, Chloride, Sulfate, Aluminum, ammonia and Phosphate. The results show that the locations of the four parameters of chlorine (CL2) with range (0.1 to 0.28) and the parameters of Ammonia with the range (0.0125 to 0.15) over the limit indicated on water quality standards. The parameters of temperature, DO, pH, brightness, nitrate, nitrite, sulfate, manganese, chloride, aluminum, iron and phosphate were still in the water quality standard PP No.82 of 2001.